A study on students' choice of an academic area / Siti Noor Hayati Mohamed Zawawi, Jamaliah Said and Kahartini Abdul Rahman - Mohamed Zawawi, Siti Noor Hayati; Said, Jamaliah; Abdul Rahman, Kahartini (Research Management Institute (RMI), 2016)
Higher education environment has become increasingly competitive and institutions have to entice for students' enrolment. Liberalization of Malaysia government policy in the higher education sector has increased the number of the higher education institutions and enrolment of students both in public and private higher education institutions. Nonetheless, the higher education institutions are faced with difficulties in recruiting the right and number of students. Thus, this study was aimed to identify the important factors that have an influence on students' choice of an academic programme and area. The data were captured using a questionnaire and only 1107 data were analysed using the SPSS software. The results from the descriptive analyses show that the students preferred most the science and technology academic area and the most important factor is the job prospect followed by the having an interest in the programme, while the important persons not surprisingly the parents, followed by the teacher that the students considered important in deciding the academic programme. The results from the Chi-Square tests show there is a statistically significant association between fees and preferred academic area; and between having an interest in the academic programme and preferred academic area, while all persons have no statistically significant associations with the preferred academic area. Finally, the male students differed significantly from the female students in terms of preferred academic area, however coincidentally, both the female and male students preferred most the science and technology area. The findings would be beneficial to the higher education authority to plan strategically and to improve on the marketing strategy for recruiting students that could align the interest of the students with that of the higher institutions and the government.